Parent and other adult practices to promote healthy eating and physical activity in children. - Hastmann, Tanis Joy (Kansas State University, 2011)
Insufficient physical activity, excessive sedentary behavior and insufficient fruit and vegetable consumption may contribute to childhood obesity. Parents and other adults provide social and physical environments, and build children’s skills for these healthful behaviors. The purpose of this dissertation was to examine parent and adult practices that contribute to the prevention of obesity in children. Chapter one reviewed the literature examining the influence of parent and adult practices on the development of young children’s eating and activity self-regulation skills. Recently, studies have provided evidence that children who lack self-regulation skills are more likely to be overweight. However, there is a gap in the literature addressing practices necessary to foster young children’s self-regulation. Thus, a need exists to identify parent and adult practices that foster the development of children’s eating and activity self-regulation skills. Chapter two described the development, validity and reliability of a self-report measure of parenting practices that may foster children’s self-regulation skills. Parents of overweight/obese children use less parenting practices that foster self-reflection of screen time than parents of normal weight children. Chapter three described the development and evaluation of an intervention designed to develop children’s self-regulation skills to ask parents for healthful home environments. The 12-week intervention was delivered to children and their parents through training child care providers. Children’s self-regulation for asking for healthy foods and activities increased after intervention, as well as increases in child eating and physical activity behaviors. In addition to parents, other adults can impact children’s environments to increase energy expenditure. Chapter four examined the influence of adult leader participation compared to no leader participation among children participating in active games. Results showed no effect of leader participation on children’s physical activity. It may be that adult participation could not increase physical activity because the children were already exhibiting high levels of moderate-to-vigorous physical activity. This dissertation provides preliminary evidence that parent/adult practices play a key role in the development of healthy eating and physical activity in children. Future research is necessary to identify the most important parent/adult practices that can be targeted by interventions to provide healthful options and build children’s skills to promote healthful behavior to prevent obesity.
Keywords: Obesity; Prevention; Parent; Home Environment; Physical Activity; Nutrition; Nutrition (0570); Public Health (0573)